A MATHEMATICAL MODEL OF DENGUE FEVER TRANSMISSION DYNAMICS INCORPORATING CLIMATE VARIABILITY AND HUMAN MOBILITY IN INDONESIA - Laelasari, Ela; Harris, Charlotte; Som, Rit (Yayasan Adra Karima Hubbi, 2025)
Dengue Fever remains a significant public health issue in Indonesia, with frequent outbreaks exacerbated by varying climatic conditions and human mobility. Understanding the dynamics of its transmission is critical to developing effective control strategies. This study aims to develop a mathematical model that incorporates climate variability and human mobility to assess the transmission dynamics of Dengue Fever in Indonesia. The model utilizes a compartmental framework, where the population is divided into susceptible, infected, and recovered individuals. The impact of climate factors such as temperature and rainfall, along with human mobility patterns, is integrated through differential equations. The study uses historical epidemiological data from the Indonesian Ministry of Health, alongside climate data from the Indonesian Meteorological Agency and human mobility data derived from mobile phone usage and transportation systems. Numerical simulations are conducted to predict the effects of climate variability and mobility on Dengue Fever outbreaks. Results indicate that both climate change and human mobility significantly influence the frequency and intensity of outbreaks, with certain regions being more vulnerable to epidemic peaks. The study concludes that incorporating environmental and social factors into epidemiological models can enhance the accuracy of Dengue Fever predictions and inform targeted intervention strategies.